Expanding the molecular spectrum and the neurological phenotype related to CAMTA1 variants. Issue 2 (23rd November 2020) - Jacobs, Eva Z.; Brown, Kathleen; Byler, Melissa C.; D'haenens, Erika; Dheedene, Annelies; Henderson, Lindsay B.; Humberson, Jennifer B.; van Jaarsveld, Richard H.; Kanani, Farah; Lebel, Robert Roger; Millan, Francisca; Oegema, Renske; et al.
Abstract: The CAMTA1 ‐associated phenotype was initially defined in patients with intragenic deletions and duplications who showed nonprogressive congenital ataxia, with or without intellectual disability. Here, we describe 10 individuals with CAMTA1 variants: nine previously unreported (likely) pathogenic variants comprising one missense, four frameshift and four nonsense variants, and one missense variant of unknown significance. Six patients were diagnosed following whole exome sequencing and four individuals with exome‐based targeted panel analysis. Most of them present with developmental delay, manifesting in speech and motor delay. Other frequent findings are hypotonia, cognitive impairment, cerebellar dysfunction, oculomotor abnormalities, and behavioral problems. Feeding problems occur more frequently than previously observed. In addition, we present a systematic review of 19 previously published individuals with causal variants, including copy number, truncating, and missense variants. We note a tendency of more severe cognitive impairment and recurrent dysmorphic features in individuals with a copy number variant. Pathogenic variants are predominantly observed in and near the N‐ and C‐ terminal functional domains. Clinical heterogeneity is observed, but 3′‐terminal variants seem to associate with less pronounced cerebellar dysfunction. Abstract :